Prime Basking Sites and Communal Basking in the Lizard, Lacerta bilineata; High Risk for Juveniles? - Roger Meek; Luca Luiselli (Diversity)
Sunlight and the heat it provides are important ecological resources for reptiles especially for those species living in temperate zones that bask extensively to maximize heat uptake. Sun basking has both benefits and costs for reptiles, giving heat that provides the energy to drive physiology but basking in open patches increases risk of predation due to higher visibility. Prime basking sites are believed to increase benefits for reptiles that include, in addition to open sunlit areas, facilitate detection of predators and prey and escape to nearby refuges. However, if such sites are limited, both inter and intra-specific interference may occur and this kind of competition may impact on a reptile’s ability to access prime basking sites, and as a consequence, its capacity to thermoregulate to optimum body temperatures. This may be especially important for juveniles, for whom rapid growth is a key factor in survivorship. We studied communal basking and interaction events at prime basking sites in the European green lizard, Lacerta bilineata, in a hedgerow in western France. We compared basking behaviour of adults and juveniles with sympatric adult wall lizards Podarcis muralis using non-invasive photographic-mark-recapture. Adult L. bilineata were more evenly distributed across basking sights compared to juveniles but significant differences were only detected between males and juveniles. Juvenile L. bilineata abandoned basking sites at the approach of both adult males and females and were aggressively removed by adult male L. bilineata. We found inter-specific communal basking between both adult and juvenile L. bilineata with adult wall lizards P. muralis. Communal basking was observed between male and female L. bilineata but not between adult males or between adult female L. bilineata. Communal basking was in proportionally greater frequency in juveniles compared to adult L. bilineata.